GENETIC CONTROL OF MORPHOLOGICAL CHARACTERS OF SEEDLINGS, BOLLS, AND SEEDS IN FLAX (LINUM USITATISSIMUM L.) - E. Porokhovinova (Вавиловский журнал генетики и селекции)
The inheritance of 14 genes has been studied by Mendelian genetic analysis. Five genes of six influencing hypocotyl color exert pleiotropic effects on other morphological characters: s1, yellow or green (s1-2) seeds, star-shaped white flower, and yellow anthers; sfbs1, white corolla of poorly pronounced star shape and yellow anthers; pbc3, star-shaped blue-tinged white flower and orange anthers; pbc1, blue-tinged white corrugated corolla and yellow anthers; f e, spotted seeds, pale blue corolla, and gray anthers. The sgh1 gene acts only in the hypocotyl. The pf1 gene (alleles pf1 and pf1-ad) changes seed color from red-brown to various shades of yellow brown, also determining pink petals and orange anthers; yspf1 acts only in the homozygote for allele pf1-ad, changing seed color to yellow; ora1 determines speckled seeds and has a pleiotropic effect on the orange color of anthers; SPS1 inhibits seed speckles in the ora1/ora1 genotype. Nonallelic genes YSED1 and ysed2 determine yellow seeds, and rs1, light yellow-brown. CSB1 controls the formation of cilia on boll septa. The interaction between most of these genes has been investigated. The pf1 and CSB1 genes demonstrate a 35-cM linkage.